Swimming Under the Radar: Trout‐Free Kōaro Populations in Aotearoa Lakes and Tarns Are Rare, Understudied, and Disappearing - Lauren G. Hitt; Simon D. Stewart; Nixie C. Boddy; Angus R. McIntosh (New Zealand Journal of Marine and Freshwater Research, 2026)
Over the last 150 years, most large, easily accessible lakes and tarns in Aotearoa (New Zealand) have experienced trout introductions or incursions, leaving few salmonid‐free reference lakes. Using database information and field surveys, we characterized lake, pond/tarn, and wetland systems found throughout Aotearoa that support populations of kōaro ( Galaxias brevipinnis ) known or putatively believed to be trout‐free. These systems require more research because our existing knowledge is outdated, patchy, and largely unacknowledged, while their kōaro populations may be increasingly vulnerable. Although persisting trout‐free kōaro populations tend to be found in small, isolated, and difficult to access lakes, at least 10% and potentially up to 22% of known trout‐free kōaro populations may have already been lost in the last 20 years. The causes of these losses are varied and highlight the sensitivity of the remaining populations, which are likely genetically isolated and evolutionarily significant. Historic and modern threats to these remaining kōaro populations include incursions of introduced fishes and worsening climate impacts. Lakes supporting isolated kōaro populations hold substantial conservation value, require more consistent monitoring to prevent additional losses of irreplaceable populations, and need targeted conservation of this important taonga (treasured species) consistent with the diversity they contribute to Aotearoa's broader freshwater biodiversity.

Balancing Harvest and Habitat: A Framework for the Sustainable Management of Diadromous Galaxiids - Ben R. J. Crichton; Michael J. H. Hickford; Angus R. McIntosh; David R. Schiel; Andrew S. Watson (New Zealand Journal of Marine and Freshwater Research, 2026)
Managing New Zealand's diadromous Galaxias species and the associated whitebait fishery presents a complex challenge due to species‐specific differences in life‐history strategies, habitat requirements, and population dynamics that underpin responses to anthropogenic and environmental pressures. Consequently, effective management must balance the distinct vulnerabilities and dependencies of each species to ensure long‐term sustainability. This complexity is evident in the fishery's differential impacts, where fishing primarily affects early life stages in kōkopu species but has broader consequences for īnanga populations. The long lifespan of kōkopu species buffers them against short‐term recruitment variation, whereas the annual life cycle of īnanga results in availability of recruits having a direct effect on adult population size. Although fishing closures support larval escapement, the overall benefit to galaxiid populations depends heavily on the quality of habitats that support post‐larval development and adult spawning. An effective management strategy should, therefore, combine targeted fishing regulations with the protection and restoration of high‐quality habitats at regional and national scales to allow sustainable recreational and cultural harvests. This dual approach is critical for sustaining īnanga populations by ensuring sufficient recruits reach adulthood, while also supporting kōkopu by maximising adult carrying capacities and overall population productivity.

Food‐web structures link multi‐scale processes in complex landscapes - Holly A. L. Harris; Jonathan D. Tonkin; Tara J. Murray; Richard F. Maloney; Angus R. McIntosh (Ecology, 2026)
Complex landscapes are challenging to study because both the higher level contextual and interacting lower level mechanistic processes underpinning their ecological characteristics occur simultaneously. However, food‐web structures can provide process insight in such landscapes by identifying these processes in specific contexts. Here, we used stable isotopes to identify spatially separate resources and infer resource flows underpinning food‐web structures in a braided river. We found that river resources used by mobile consumers, including birds and fish, were spatially heterogeneous. Consumer resource use was related to four key structural food‐web attributes: (1) spatiotemporal variation in foraging, (2) subsidies, (3) omnivory, and (4) ontogenetic niche shifts. Thus, both physical heterogeneity (contextual physical processes) and adaptive characteristics of consumers (mechanistic processes) were likely contributing to important food‐web structures. Identifying these food‐web structures in landscapes, across scales of resource use and spatial distribution, provides a way to identify processes and scales likely contributing to food‐web stabilization.

Looks Can Be Deceiving: Morphological Traits Are Weakly Associated With the Isotopic Niches of Freshwater Fishes - Julian D. Olden; Friedrich W. Keppeler; Timothy D. Jardine; Stéphanie Boulêtreau; Chris Harrod; Michelle C. Jackson; Angus R. McIntosh; Marie‐Elodie Perga; Josie South; Pablo Tedesco; Chloé Vagnon; Julien Cucherousset (Global Ecology and Biogeography, 2025)
Aim Fueled by the emergence of global‐scale databases, fish morphological traits are now routinely used as a proxy for trophic ecology when estimating functional diversity. Yet, a rigorous empirical validation of trophic‐morphology relationships is lacking. This study offers a global test of whether species' morphology is associated with a known indicator of trophic ecology, stable isotope ratios of carbon and nitrogen. Location Worldwide. Time Period 1992–2023. Major Taxa Studied Freshwater fishes (Actinopterygii). Methods Isotope‐morphology relationships were examined using δ 13 C and δ 15 N values from 811 fish communities and ten species‐level morphological traits with direct relevance for foraging behaviour (body length, body shape, and position of the mouth, eyes and fins) for 1282 species. Associations were assessed with Multiple Regression on Distance Matrices and Multivariate Generalised Linear Models (MGLM). Analyses were repeated at the individual level for five fish species. Results Species morphological similarities explained, on average, 10% of the variation in stable isotope values for fish communities, with > 6% of the communities exhibiting statistically significant associations. The MGLM explained 53% of the variation in δ 13 C and 48% in δ 15 N, with approximately 97% and 77% of this variation, respectively, attributed to the site identity (random effect), not the morphological traits. Individual traits contributed minimally (each δ 15 N, while no significant differences were observed for δ 13 C. At the individual level, morphology explained 0% to 16% of isotopic variation within populations, averaging 4%. Main Conclusions Weak isotope‐morphology relationships for freshwater fishes may arise from the influence of a host of biological, environmental, or methodological factors, or may truly indicate a fundamental disconnection between morphological traits measured at the species level and the trophic niche of populations that are manifested in food webs. Ecologists should recognise the limitations of assuming morphological traits are ‘functional’ in the sense that they can offer a reasonable proxy of a species' trophic ecology at large scales.

Ecosystem-size relationships of river populations and communities - Angus R. McIntosh; Hamish S. Greig; Helen J. Warburton; Jonathan D. Tonkin; Catherine M. Febria (Trends in Ecology & Evolution, 2024)

Recreational Disturbance of River Sediments During Base Flow Deteriorates Microbial Water Quality - Isabelle Pattis; Elaine Moriarty; Juliet Anderson; Angus McIntosh; Brent Gilpin (International Journal of Environmental Research, 2024)

Correction to: Community type and disturbance type interact to determine disturbance response: implications for extending the environmental filter metaphor - Isabelle C. Barrett; Angus R. McIntosh; Helen J. Warburton (Community Ecology, 2023)

Community type and disturbance type interact to determine disturbance response: implications for extending the environmental filter metaphor - Isabelle C. Barrett; Angus R. McIntosh; Helen J. Warburton (Community Ecology, 2023)
Ecological disturbances act as environmental filters by removing species with particular characteristics, resulting in community types associated with different disturbance histories. However, studies to date on community responses to disturbance have neglected the potential for different community assemblages to display different responses. Using lotic invertebrate communities as a study system, this study investigated the influence of community composition on disturbance response. We undertook a 26-h stream channel experiment to test how distinct invertebrate community types (an undisturbed spring community, flood-disturbed community, and agriculture-disturbed community), shaped by specific disturbance histories and characterised by different species with particular functional groups, responded to additional disturbance of varying types and combinations (an undisturbed control, high-flow, nutrients, sediment, and a combined sediment and nutrients treatment). Invertebrate drift was used as a diagnostic tool to assess community responses. Significant three-way interactions were identified for total invertebrate drift, drift of typically sensitive taxa (Ephemeroptera, Plecoptera and Trichoptera) and drift of cased organisms between community type, disturbance type and time, indicating that disturbance history and corresponding community type influenced community response to disturbance. Differing responses to disturbance between community types were often characterised by specific taxa, likely driven by adaptive traits, but also by phenotypic plasticity and altered biotic interactions. Community responses to the multiple disturbance scenario suggested potential for interactive effects, with differing responses potentially driven by species co-tolerance mechanisms. When determining the impacts of disturbance, our results suggest there is insight to be gained from a broader perspective incorporating multiple community types into future research. This approach could also improve management outcomes, facilitating tailored restoration and conservation strategies.

Trait variation in a successful global invader: a large-scale analysis of morphological variance and integration in the brown trout - Matthias Vignon; Mingsha Zhou; Angus R. McIntosh; Cristian Correa; Peter A. H. Westley; Lisa Jacquin; Jacques Labonne; Andrew P. Hendry (Biological Invasions, 2023)

Riparian plant species offer a range of organic resources to stream invertebrate communities through varied leaf breakdown rates - Kristy Hogsden; Sophie O'Brien; Stacey Bartlett; Helen Warburton; Hayley Devlin; Kathryn Collins; Catherine Febria; Brandon Goeller; Angus McIntosh; Jon Harding (New Zealand Journal of Marine and Freshwater Research, 2023)
Riparian plants provide an important source of energy for freshwater food webs through inputs of leaf litter. Planting riparian buffers with mixed species could enhance the detrital resource supply for invertebrates through varied leaf breakdown rates. To quantify leaf breakdown rates and invertebrate colonisation, we used leaves from eleven grass, shrub and tree species common along agricultural waterways in New Zealand. Breakdown of leaves immersed in a spring‐fed stream differed significantly among species, being fastest for pasture grass ( k = 0.0458 day −1 ) followed by broadleaf, pittosporum, willow, toetoe, poplar, gorse, Carex , eucalyptus, flax, and slowest for cabbage tree leaves ( k = 0.0099 day −1 ). Invertebrate community composition did not differ between leaf species, but consumers were extremely abundant on some leaves (e.g. 51–83 Potamopyrgus snails g −1 pasture grass), indicating coarse detrital resources were in high demand for food or habitat. These breakdown rates could inform selection of riparian plant combinations that will enhance food availability for stream communities, especially continuity of supply, thereby contributing to waterway restoration.

Habitat size influences community stability - Hamish S. Greig; Peter A. McHugh; Ross M. Thompson; Helen J. Warburton; Angus R. McIntosh (Ecology, 2022)
Mechanisms linked to demographic, biogeographic, and food‐web processes thought to underpin community stability could be affected by habitat size, but the effects of habitat size on community stability remain relatively unknown. We investigated whether those habitat‐size‐dependent properties influenced community instability and vulnerability to perturbations caused by disturbance. This is particularly important given that human exploitation is contracting ecosystems, and abiotic perturbations are becoming more severe and frequent. We used a perturbation experiment in which 10 streams, spanning three orders of magnitude in habitat size, were subjected to simulated bed movement akin to a major flood disturbance event. We measured the resistance, resilience, and variability of basal resources, and population and community‐level responses across the stream habitat‐size gradient immediately before, and at 0.5, 5, 10, 20, and 40 d post‐disturbance. Resistance to disturbance consistently increased with stream size in all response variables. In contrast, resilience was significantly higher in smaller streams for some response variables. However, this higher resilience of small ecosystems was insufficient to compensate for their lower resistance, and communities of smaller streams were thus more variable over time than those of larger streams. Compensatory dynamics of populations, especially for predators, stabilized some aspects of communities, but these mechanisms were unrelated to habitat size. Together, our results provide compelling evidence for the links between habitat size and community stability, and should motivate ecologists and managers to consider how changes in the size of habitats will alter the vulnerability of ecosystems to perturbations caused by environmental disturbance.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Heterogeneity in flow disturbance around river confluences influences spatial patterns in native and non-native species co-occurrence - Nixie C. Boddy; Doug J. Booker; Angus R. McIntosh (Biological Invasions, 2020)

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Drought survival is a threshold function of habitat size and population density in a fish metapopulation - Richard S. A. White; Peter A. McHugh; Angus R. McIntosh (Global Change Biology, 2016)
Because smaller habitats dry more frequently and severely during droughts, habitat size is likely a key driver of survival in populations during climate change and associated increased extreme drought frequency. Here, we show that survival in populations during droughts is a threshold function of habitat size driven by an interaction with population density in metapopulations of the forest pool dwelling fish, Neochanna apoda . A mark–recapture study involving 830 N. apoda individuals during a one‐in‐seventy‐year extreme drought revealed that survival during droughts was high for populations occupying pools deeper than 139 mm, but declined steeply in shallower pools. This threshold was caused by an interaction between increasing population density and drought magnitude associated with decreasing habitat size, which acted synergistically to increase physiological stress and mortality. This confirmed two long‐held hypotheses, firstly concerning the interactive role of population density and physiological stress, herein driven by habitat size, and secondly, the occurrence of drought survival thresholds. Our results demonstrate how survival in populations during droughts will depend strongly on habitat size and highlight that minimum habitat size thresholds will likely be required to maximize survival as the frequency and intensity of droughts are projected to increase as a result of global climate change.

Increases in disturbance and reductions in habitat size interact to suppress predator body size - Phillip G. Jellyman; Peter A. McHugh; Angus R. McIntosh (Global Change Biology, 2014)
Food webs are strongly size‐structured so will be vulnerable to changes in environmental factors that affect large predators. However, mechanistic understanding of environmental controls of top predator size is poorly developed. We used streams to investigate how predator body size is altered by three fundamental climate change stressors: reductions in habitat size, increases in disturbance and warmer temperatures. Using new survey data from 74 streams, we showed that habitat size and disturbance were the most important stressors influencing predator body size. A synergistic interaction between that habitat size and disturbance due to flooding meant the sizes of predatory fishes peaked in large, benign habitats and their body size decreased as habitats became either smaller or harsher. These patterns were supported by experiments indicating that habitat‐size reductions and increased flood disturbance decreased both the abundance and biomass of large predators. This research indicates that interacting climate change stressors can influence predator body size, resulting in smaller predators than would be predicted from examining an environmental factor in isolation. Thus, climate‐induced changes to key interacting environmental factors are likely to have synergistic impacts on predator body size which, because of their influence on the strength of biological interactions, will have far‐reaching effects on food‐web responses to global environmental change.

Aquatic Macrophytes Alter Metabolism and Nutrient Cycling in Lowland Streams - Jonathan M. O’Brien; Joanna L. Lessard; David Plew; S. Elizabeth Graham; Angus R. McIntosh (Ecosystems, 2014)

Limitation and facilitation of one of the world's most invasive fish: an intercontinental comparison - Phaedra Budy; Gary P. Thiede; Javier Lobón-Cerviá; Gustavo Gonzalez Fernandez; Peter McHugh; Angus McIntosh; Lief Asbjørn Vøllestad; Eloy Becares; Phillip Jellyman (Ecology, 2013)
Purposeful species introductions offer opportunities to inform our understanding of both invasion success and conservation hurdles. We evaluated factors determining the energetic limitations of brown trout ( Salmo trutta ) in both their native and introduced ranges. Our focus was on brown trout because they are nearly globally distributed, considered one of the world's worst invaders, yet imperiled in much of their native habitat. We synthesized and compared data describing temperature regime, diet, growth, and maximum body size across multiple spatial and temporal scales, from country (both exotic and native habitats) and major geographic area (MGA) to rivers and years within MGA. Using these data as inputs, we next used bioenergetic efficiency (BioEff), a relative scalar representing a realized percentage of maximum possible consumption (0–100%) as our primary response variable and a multi‐scale, nested, mixed statistical model (GLIMMIX) to evaluate variation among and within spatial scales and as a function of density and elevation. MGA and year (the residual) explained the greatest proportion of variance in BioEff. Temperature varied widely among MGA and was a strong driver of variation in BioEff. We observed surprisingly little variation in the diet of brown trout, except the overwhelming influence of the switch to piscivory observed only in exotic MGA. We observed only a weak signal of density‐dependent effects on BioEff; however, BioEff remained 2.5 fish/m 2 . The trajectory of BioEff across the life span of the fish elucidated the substantial variation in performance among MGAs; the maximum body size attained by brown trout was consistently below 400 mm in native habitat but reached ∼600 mm outside their native range, where brown trout grew rapidly, feeding in part on naive prey fishes. The integrative, physiological approach, in combination with the intercontinental and comparative nature of our study, allowed us to overcome challenges associated with context‐dependent variation in determining invasion success. Overall our results indicate “growth plasticity across the life span” was important for facilitating invasion, and should be added to lists of factors characterizing successful invaders.

Niche flexibility and trout–galaxiid co-occurrence in a hydrologically diverse riverine landscape - Peter McHugh; Angus McIntosh; Simon Howard; Phaedra Budy (Biological Invasions, 2012)

Dual influences of ecosystem size and disturbance on food chain length in streams - Peter A. McHugh; Angus R. McIntosh; Phillip G. Jellyman (Ecology Letters, 2010)
Ecology Letters (2010) 13: 881–890 Abstract The number of trophic transfers occurring between basal resources and top predators, food chain length (FCL), varies widely in the world’s ecosystems for reasons that are poorly understood, particularly for stream ecosystems. Available evidence indicates that FCL is set by energetic constraints, environmental stochasticity, or ecosystem size effects, although no single explanation has yet accounted for FCL patterns in a broad sense. Further, whether environmental disturbance can influence FCL has been debated on both theoretical and empirical grounds for quite some time. Using data from sixteen South Island, New Zealand streams, we determined whether the so‐called ecosystem size, disturbance, or resource availability hypotheses could account for FCL variation in high country fluvial environments. Stable isotope‐based estimates of maximum trophic position ranged from 2.6 to 4.2 and averaged 3.5, a value on par with the global FCL average for streams. Model‐selection results indicated that stream size and disturbance regime best explained across‐site patterns in FCL, although resource availability was negatively correlated with our measure of disturbance; FCL approached its maximum in large, stable springs and was

Predator effects on prey population dynamics in open systems - Barbara L. Peckarsky; Billie L. Kerans; Brad W. Taylor; Angus R. McIntosh (Oecologia, 2008)

Persistence of a significant population of rare Canterbury mudfish ( Neochanna burrowsius ) in a hydrologically isolated catchment - Jon S. Harding; David A. Norton; Angus R. McIntosh (New Zealand Journal of Marine and Freshwater Research, 2007)
Canterbury mudfish ( Neochanna burrowsius ) are endemic to a small region of Canterbury, South Island, New Zealand and classified as nationally endangered. We reviewed data from the New Zealand Freshwater Fish Database and trapped fish in July 2006, and January and February 2007 in the Waianiwaniwa Valley, Canterbury to determine the importance of this catchment for mudfish conservation. Mudfish were found in 19 of the 28 sites sampled. Waianiwaniwa Valley sites accounted for 47% of all Canterbury mudfish database records of mean catch per unit effort (CPUE) ≥6 fish. The population comprised young recruits ( 120mm TL) indicating a healthy population. Drying of the lower mainstem, and low dissolved oxygen levels in summer create a unique catchment free of larger predatory fish and with reduced competition from other fish species. We estimated that mudfish occur in at least 24.3 km of the Waianiwaniwa River, making this catchment the most important refuge known for the conservation of this species.

Spatial Modeling and Habitat Quantification for Two Diadromous Fish in New Zealand Streams: A GIS-Based Approach with Application for Conservation Management - Hans S. Eikaas; Andrew D. Kliskey; Angus R. Mcintosh (Environmental Management, 2005)

Top-down and bottom-up processes in grassland and forested streams - Per Nyström; Angus R. McIntosh; Michael J. Winterbourn (Oecologia, 2003)

Are impacts of an exotic predator on a stream food web influenced by disturbance history? - Per Nyström; Angus R. McIntosh (Oecologia, 2003)

Swarming and mating behavior of a mayfly Baetis bicaudatus suggest stabilizing selection for male body size - Barbara L. Peckarsky; Angus R. McIntosh; Christopher C. Caudill; Jonas Dahl (Behavioral Ecology and Sociobiology, 2002)

Reach‐scale manipulations show invertebrate grazers depress algal resources in streams - Brad W. Taylor; Angus R. McIntosh; Barbara L. Peckarsky (Limnology and Oceanography, 2002)
Experimental tools that enable manipulations of organisms at larger scales allow for comparisons of processes across multiple spatial scales and expand our ability to make predictions about ecological processes. We performed reach scale (i.e., 50 m 2 ) manipulations of invertebrate communities in streams using a modified electroshocking technique to nondestructively remove invertebrates. In addition, we conducted a microcosm experiment (i.e., 157 cm 2 ) with different grazer densities that enabled comparison of the strength of grazer‐algal interactions at large and small spatial scales. In high elevation headwater streams, electroshocking reduced total invertebrate abundance by 84% in a 50‐m 2 reach of stream. Although mobile invertebrates recolonized the manipulated area rapidly, daily electroshocking maintained the density reduction. Electroshocking reduced the density of herbivorous invertebrates 86%, which resulted in a 57% increase in algal biomass, whereas in a stream that was not electroshocked, invertebrate density and algal biomass changed much less, only 16 and 8%, respectively. Comparison of grazer effect on periphyton between microcosm and reach‐scale experiments revealed that the per capita interaction strength of grazers on primary producers was three times greater in the reach‐scale manipulation than that observed in the microcosm experiments. Reach‐scale manipulation of invertebrate grazers in streams provides a powerful method to experimentally test patterns observed in the field at a large spatial scale, with more realism than streamside microcosms or small cages in streams.

Hook up on snapper. By MarkKitteridge. Published in 2000 by Reed Publishing (NZ) Ltd, 39 Rawene Road, Private Bag 34 901, Birkenhead, Auckland 10, New Zealand (http://www.reed.co.nz). 127 p., limpbound. ISBN: 0–7900–0756–8. Price: NZ$29.95 (orders: info@reed.co.nz).Reed field guide to New Zealand freshwater fishes. By R. M.McDowall. Published in 2000 by Reed Publishing (NZ) Ltd, 39 Rawene Road, Private Bag 34 901, Birkenhead, Auckland 10, New Zealand (http://www.reed.co.nz). 224 p., hardback. ISBN: 0–78900–0725–8. Price: NZ$39.95 (orders: info@reed.co.nz). - Trevor J. Willis; Angus R. Mcintosh (New Zealand Journal of Marine and Freshwater Research, 2001)

Rapid size-specific changes in the drift of Baetis bicaudatus (Ephemeroptera) caused by alterations in fish odour concentration - Angus R. McIntosh; Barbara L. Peckarsky; Brad W. Taylor (Oecologia, 1999)

Fitness and community consequences of avoiding multiple predators - Barbara L. Peckarsky; Angus R. McIntosh (Oecologia, 1998)